Partisipasi Komite Sekolah Dalam Pengembangan Pendidikan Di Smp Negeri 2 Kalijambe - Raqib, Muhammad; , Prof. Dr. Yetty Sardjono, M.Si; , Dr. Sabar Narimo, M.M., M.Pd (2015)
The aim of this research are. 1) obtain an overview of the role of the school committee and the school established a policy in the education development at SMP Negeri 2 Kalijambe, 2) determine the sources of finance in the education development at SMP Negeri 2 Kalijambe, 3) find a school committee participation in formulation, implementation and evaluation policy of the Plan Budget School at SMP Negeri 2 Kalijambe. This research is a qualitative research with naturalistic paradigm approach. The location of this research at SMP Negeri 2 kalijambe. Data was collected by interview, observation and document. Data analysis technique using an interactive model analysis. Results of this research, are: 1) The role of schools and school committees in education funding policy at junior high school include the components that should be funded by the school in order to provide education. 2) Sources of finance in the development of education at junior high schools are funds from the government and BOS (School Operational Assistance). 3) School committee participation in formulation, implementation and evaluation policy of the Plan Budget School at junior high school are a) School Committee participation as giving advisory; b) School Committee participation as supporter; c) School Committee participation as controller; and d) School Committee participation as mediator